Communication and information model of the inclusion of digital participation in the evaluation of social processes - S. V. Shekshuev (Цифровая социология)
The evolution and wide use of modern technologies, tools and methods of communication are an integral part of the modern information society. In particular, current communication and information technologies provide an opportunity to create and extract a digital footprint for an individual or a certain group. In relation to the public authorities’ activities, the digital footprint can be used to analyse the reaction of society to their actions more effectively. By researching the digital footprint of social media actors in a particular region, it is possible to determine how the population treats various decisions and measures taken by the authorities. Due to digital participation, citizens have the opportunity and a tool to facilitate the management process at the stages of decision-making. The digital participation generates a digital footprint, the analysis of which provides feedback on the actions of the authorities. The purpose of the article is to propose a communicative and information model for the inclusion of the digital participation in the evaluation of social processes, consisting of mechanisms and interfaces for obtaining information alongside with mechanisms and interfaces for receiving feedback for evaluating the activities of public authorities in the region. The efficiency of the model has been practically proved by the example of a socially significant event in the Oryol region. Using the example of regional management centres, the expediency of introducing the model for evaluating the activities of public authorities in the region through receiving feedback is shown. This will increase the involvement of citizens in the regulation of social processes in the region and improve the quality of management.